2015
DOI: 10.1177/0885328215589205
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing spinal dura-like tissue using electrospun poly(lactide-co-glycolide) membranes and dermal fibroblasts to seamlessly repair spinal dural defects in goats

Abstract: Many neuro- and spinal surgeries involving access to the underlying nervous tissue will cause defect of spinal dural mater, further resulting in cerebrospinal fluid leakage. The current work was thus aimed to develop a package which included two layers of novel electrospun membranes, dermal fibroblasts and mussel adhesive protein for repairing spinal dural defect. The inner layer is electrospun fibrous poly(lactide-co-glycolide) membrane with oriented microstructure (O-poly(lactide-co-glycolide)), which was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…Electrospun dural substitutes have now been explored due to their ECM‐like structure. Furthermore, they can be further modified to increase fibroblast migration, adhesion, and proliferation (Ma et al, 2021; Yu et al, 2015). This feature is particularly important in dural repair as dural fibroblasts can accelerate wound closure following implantation, therefore preventing any further CSF leakage at the injury site.…”
Section: Examples Of Drug‐loaded Electrospun Scaffold In Neural Injuriesmentioning
confidence: 99%
“…Electrospun dural substitutes have now been explored due to their ECM‐like structure. Furthermore, they can be further modified to increase fibroblast migration, adhesion, and proliferation (Ma et al, 2021; Yu et al, 2015). This feature is particularly important in dural repair as dural fibroblasts can accelerate wound closure following implantation, therefore preventing any further CSF leakage at the injury site.…”
Section: Examples Of Drug‐loaded Electrospun Scaffold In Neural Injuriesmentioning
confidence: 99%
“…As a result, various synthetic polymers such as poly lactic acid (PLA), polyurethane (PU), polyethylene glycol (PEG), poly-E-caprolactone (PCL), poly (3-hydroxybutyrate-co-3 hydroxyvalerate (PHBV), polyglycolic acid (PGA), and etc. have been applied for synthesizing dural substitutes [ 52 , 66 , 67 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ]. Although synthetic polymers possess sufficient mechanical properties, most of them are rejected due to local tissue reactions, excessive scar formation, meningitic symptoms, etc.…”
Section: Biomedical Applications Of Electrospun Nanofibersmentioning
confidence: 99%
“…15,16 There have also been a lot of studies on the preparation of dura repair materials using electrospinning technology. [17][18][19] Moreover, research has demonstrated the superior overall qualities of biodegradable synthetic materials for dura repair, such as polylactic acid (PLA), polycaprolactone (PCL), polylactic acid-glycolic acid (PLGA), and polyurethane (PU) produced by electrospinning technology. [20][21][22] The FDA has also approved PLA and PCL as implantable degradable polymer materials.…”
Section: Introductionmentioning
confidence: 99%